LOYALITAS NASABAH DARI KEMUDAHAN PENGGUNAAN MOBILE BANKING - Evi Susanti; Novita Oktavianti Parera (International Journal of Digital Entrepreneurship and Business, 2021)
The research purpose is to examine customer loyalty from the variable of mobile banking usability mediated by customer satisfaction. Data were collected in a survey of M-Banking customers conducted from February to August 2020 via a questionnaire involving 105 respondents. The results showed that the ease of using M-Banking lead to customer satisfaction and also lead to bank loyalty, respectively. Considering the change in customer consumption patterns to using technology-based services, banks as service providers need to deliver service in easily, safely, and fast ways, such as internet banking and M-Banking. The research originality examines the direct effect of usability on customer loyalty, especially in conventional banks in Jakarta Province.